APLIKASI METAL-ORGANIC FRAMEWORKS (MOF) BERBASIS LOGAM Zn DALAM DEGRADASI FOTOKATALITIK POLUTAN ORGANIK - Ananda Fitra Yuda; Husna Syaima (PROSIDING SEMINAR KIMIA, 2025)
Photocatalytic degradation is a widely studied method for reducing the concentration of organic pollutants. This technique has proven effective in breaking down various organic compounds, including dyes, pharmaceuticals, and pesticides. Metal-Organic Frameworks (MOFs) represent a promising class of materials for photocatalytic degradation due to their favorable catalytic properties, such as high porosity and large surface area. Additionally, MOFs offer structural tunability, allowing their properties to be tailored for specific applications. This review discusses the structural characteristics, photocatalytic mechanisms, synthesis strategies, current applications, and the future prospects and challenges of Zn-based MOFs in the photocatalytic degradation of organic pollutants.   Keywords: Metal-Organic Frameworks, Zinc, Photocatalytic Degradation